2014
DOI: 10.1186/1471-227x-14-16
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing readiness to deploy in disaster response: findings from a cross-sectional survey of the Department of Veterans Affairs Disaster Emergency Medical Personnel System

Abstract: BackgroundThe Disaster Emergency Medical Personnel System (DEMPS) program provides a system of volunteers whereby active or retired Department of Veterans Affairs (VA) personnel can register to be deployed to support other VA facilities or the nation during national emergencies or disasters. Both early and ongoing volunteer training is required to participate.MethodsThis study aims to identify factors that impact willingness to deploy in the event of an emergency. This analysis was based on responses from 2,38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…Additionally, women healthcare workers were reported to be less willing to respond during a disaster, especially during epidemics [2,13,21]; and younger respondents were more likely to be absent than their older colleagues [2,16]. Women VA volunteers within the Disaster Emergency Medical Personnel System (DEMPS) program were also somewhat less ready to deploy in the event of a disaster compared to men, perhaps due to disproportionate responsibilities for caregiving [39]. It is also possible that the observed gender differences are due to differences in risk-taking behaviors between men and women [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, women healthcare workers were reported to be less willing to respond during a disaster, especially during epidemics [2,13,21]; and younger respondents were more likely to be absent than their older colleagues [2,16]. Women VA volunteers within the Disaster Emergency Medical Personnel System (DEMPS) program were also somewhat less ready to deploy in the event of a disaster compared to men, perhaps due to disproportionate responsibilities for caregiving [39]. It is also possible that the observed gender differences are due to differences in risk-taking behaviors between men and women [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The disaster exercise confirmed that large numbers of team members were available when called on to be deployed. The availability rate of 79% demonstrated in the disaster exercise, is higher than the 50% availability rate observed among disaster response workers elsewhere (Zagelbaum et al, 2014). This difference was likely due to the unique purpose of the DRST, the recruitment procedures and ongoing rotations, and the commitment and ownership that the nurses felt towards the partnership.…”
Section: Discussionmentioning
confidence: 39%
“…In general, other studies have suggested that an ancillary benefit to any education or training program may be improved volunteer satisfaction, commitment, confidence, and willingness to continue to participate. 6,9,18 The current study has also demonstrated that more participation in training (based on number of modes) and deployment can improve volunteers' willingness to continue in DEMPS or recommend it to others. Participants specifically noted in their written responses that training and field exercises could keep volunteers involved in the program.…”
Section: Discussionmentioning
confidence: 59%